Cold weather construction materials : Part 2 : Regulated-set cement for cold weather concreting - Houston, Billy J.; Hoff, G. C. (George C.); Structures Laboratory (U.S.); Cold Regions Research and Engineering Laboratory (U.S.); United States. Army. Office of the Chief of Engineers. (Vicksburg, Miss. : The Station, 1981)
"Monitored by U.S. Army Cold Regions Research and Engineering Laboratory." "Prepared for Office, Chief of Engineers, U.S. Army under DA Project 4K078012AAM1, Task 00, Work Unit 004." "September 1981." Cover title. Final report. Mode of access: Internet.